2019
DOI: 10.3399/bjgp19x707237
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a primary care-based opioid and pain review service: a mixed-methods evaluation in two GP practices in England

Abstract: BackgroundOpioid prescribing to treat chronic non-cancer pain has rapidly increased, despite a lack of evidence for long-term safety and effectiveness. A pain review service was developed to work with patients taking opioids long-term to explore opioid use, encourage non-drug-based alternatives, and, where appropriate, support dose reduction.AimTo evaluate the service and its potential impact on opioid use, health and wellbeing outcomes, and quality of life (QoL).Design and settingMixed-methods evaluation of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…32 CCGs with elevated prescribing levels observed in some but not all areas could benefit from practice and community based interventions which could lead to a reduction in opioid use and improvement in health outcomes of people treated with opioids. 33 In the face of no one-size-fits-all intervention successful at improving opioid prescribing patterns, 17 evidence provided in this study can guide policy designers in ensuring that appropriate resources are allocated where they can bring the most benefits.…”
Section: Discussionmentioning
confidence: 96%
“…32 CCGs with elevated prescribing levels observed in some but not all areas could benefit from practice and community based interventions which could lead to a reduction in opioid use and improvement in health outcomes of people treated with opioids. 33 In the face of no one-size-fits-all intervention successful at improving opioid prescribing patterns, 17 evidence provided in this study can guide policy designers in ensuring that appropriate resources are allocated where they can bring the most benefits.…”
Section: Discussionmentioning
confidence: 96%
“…An article published in February 2020 by Scott et al [ 31 ▪ ] evaluated a primary care-based opioid and pain review service using a mixed methods approach. In the United Kingdom, primary care refers to the management of patients with a general practice setting, which is where the majority of patients are managed unless they require specialist treatment.…”
Section: Effectiveness Of Novel Opioid and Pain Review Servicesmentioning
confidence: 99%
“…In total, 34 patients enrolled in the novel service and a decrease in median prescribed opioid dose was observed from baseline ( P < 0.0001). Improvements in health, wellbeing and quality of life were also observed [ 31 ▪ ]. The authors concluded that the service was well received overall and appeared to have potential benefits, warranting further exploration of this care pathway through a randomized controlled trial.…”
Section: Effectiveness Of Novel Opioid and Pain Review Servicesmentioning
confidence: 99%
“…In England, if every general practice prescribed highdose opioids at the same rate as the lowest decile of practices, a cost saving of £24.8 million and 543,000 fewer high-dose opioid prescriptions could be achieved in 6 months [5]. Thus, investing in resources and programs tailored to people taking opioids in primary care such as the service evaluated by Scott et al [53] could reduce the need for people on high doses to visit emergency departments.…”
Section: Implications For Practice and Policymentioning
confidence: 99%